The Radiosensitizing Effect of Tumor-Derived Microparticles Co-Loaded with Sorafenib and Gold Nanoparticles on Hepatocellular Carcinoma - Yu L; Liu J; Fan Y; Hu X; Zeng X; Luo S; Chen P (International Journal of Nanomedicine)
Li Yu,1,2,* Jiali Liu,1,* Yiwen Fan,1,* Xiao Hu,1,3 Xiaonan Zeng,1 Shan Luo,4 Ping Chen1 1Department of Oncology, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 2Department of Oncology, Jiangsu Cancer Hospital, Nanjing Medical University Affiliated Cancer Hospital, Nanjing, Jiangsu, 210009, People’s Republic of China; 3Oncology Treatment Center, People’s Hospital of Yangjiang Affiliated to Guangdong Medical University, Yangjiang, Guangdong, 529500, People’s Republic of China; 4Tianfu Jincheng Laboratory, Chengdu, 610212, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ping Chen, Department of Oncology, the Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China, Email biochenp@126.comObjective: Hepatocellular carcinoma (HCC) is a highly heterogeneous tumor with features such as high recurrence, easy metastasis, and poor prognosis, posing significant challenges for clinical treatment. In this study, we introduce a novel approach for treating HCC using tumor cell-derived microparticles (MPs) co-loaded with sorafenib and gold nanoparticles (AuNP) in combination with radiotherapy.Methods: MPSF@AuNP was prepared by co-incubating AuNP with sorafenib, and was evaluated using dynamic light scattering (DLS), transmission electron microscopy (TEM), ultraviolet-visible spectrophotometry (UV-Vis), inductively coupled plasma optical emission spectrometry (ICP-OES), high-performance liquid chromatography (HPLC), and SDS-PAGE electrophoresis. Subsequently, their targeting ability toward hepatocellular carcinoma cells and their combined antitumor therapeutic effects with radiotherapy were investigated through in vitro and in vivo experiments, while their in vivo safety was also assessed.Results: Our results demonstrate that co-loaded microparticles (MPSF@AuNP) can effectively deliver therapeutic agents to tumor cells through homologous targeting, improving the bioavailability of therapeutic drugs and enhancing their cytotoxicity against tumor cells. Furthermore, the combination of MPSF@AuNP with radiotherapy shows a synergistic anti-tumor effect by enhancing the inhibition of tumor cell proliferation, promoting tumor cell apoptosis, remodeling the tumor microenvironment, and activating the anti-tumor immune responses.Conclusion: This study offers a promising treatment approach for malignant tumors such as HCC by using MP co-loaded and delivered with anti-tumor drugs and AuNP in combination with radiotherapy.Keywords: hepatocellular carcinoma, HCC, tumor-derived microparticles, MPs, sorafenib, gold nanoparticles, AuNP